Effect of Nitrogen and Zinc on Growth and Yield of Maize (Zea mays L.) - Singh, Jagdeep; Partap, Ram; Singh, Amritpal; kumar, Naresh; Krity (International Journal of Bio-resource and Stress Management, 2021)
The experiment was laid out on the effect of nitrogen and zinc on growth and yield of maize (Zea mays L.) at Research Farm of the Department of Agriculture, Mata Gujri College, Fatehgarh Sahib, Punjab, India during kharif (July to October) season of 2017. The experiment was laid out in randomized block design three replication with eight treatments. The soil of the experimental field was Gangetic alluvial having clay loam texture with pH 7.5. It was moderately fertile, with available nitrogen (285.24 kg ha-1), available phosphorus (26.15 kg ha-1), available potassium (250.84 kg ha-1) and available zinc (1.42 mg kg-1). The maximum growth parameter viz. plant height (cm), LAI (%), dry matter accumulation (g) and the highest yield attributes and yield parameters viz., number of cob-1, length of cob (cm), test weight (g), number of grain cob-1, grain yield (q ha-1), stover yield (q ha-1), biological yield (q ha-1) and harvest index (%) was recorded at 30, 60, 90 DAS and at harvest stage with the application of nitrogen @150 kg ha-1++zinc @30 kg ha-1 which was at par with the treatments namely; nitrogen @150 kg ha-1++zinc @15 kg ha-1 and nitrogen @150 kg ha-1. All the treatments significantly influenced the growth and yield attributes as compared to control. The maximum net returns (Rs. 89977 ha-1) and benefit:cost ratio (1.58) has been recorded with application of nitrogen @150 kg ha-1++zinc @30 kg ha-1.